Research Paper: Effect of Eight Weeks Corrective Games on Kyphosis Curve and Strengths of Trunk Muscle in Kyphotic Mentally Retarded Children - Leila Ahmadnezhad; Ahmad Ebrahimi- Atri; Nahid Khoshraftar-Yazdi; Yahya Sokhangoei (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective In our community, there are many children and adults who have certain distinctive aspects of mental, physical, emotional, or behavioral characteristics. The purpose of this study was to examine the effect of eight weeks play therapy program on the balance of the mentally retarded children. On this basis according to the needs of the children to play for freshness and lack of research in the field of corrective exercise in a game formats  Materials & Methods Thirty mentally retarded girl children with increased normal thoracic kyphosis (kyphosis angle≥40) were selected and randomly divided into two groups; training group (n=15 with mean[SD] age 12.06[2.8] y, mean[SD]height 1.4[0.1] m, mean[SD]weight 42.3[1.3] kg) and control group (n=15 with mean[SD] age 12.26[2.8] y, mean[SD]height 1.4[0.9] m, mean[SD]weight 43.6[1.3] kg). The angle of kyphosis was measured using a flexible ruler, and the dynamometer was used to evaluate the strengths of trunk muscle. The experimental group performed corrective games for a period of eight weeks (three sessions per week), and during this period, the control group did not perform any exercises. Independent and dependent t-tests were used to analyze the data. All statistical analyses were performed using SPSS statistical software version 16, and the significance level was set at 0.05. Results The results of the research showed that corrective games had a significantly positive effect on the kyphosis Angle (P=0.001, t=4.41) and the strength of trunk muscle (P=0.004, t=3.15) in mentally retarded children.  Conclusion Corrective games can improve kyphosis curve and strength of trunk muscles in mentally retarded children. Based on the results of this research on the corrective effect of play therapy on kyphosis curve and strength of trunk muscle in kyphotic mentally retarded children who need to have an independent living and get rid of physical abnormalities, it is recommended to do play therapy protocols to improve physical abnormalities.